Supporting Quality Education: The Influence of Principal Supportive Leadership and School Environment on Teacher Work Motivation - Evita Maila Sari; Ahmad Subandi; Nellitawati; Hanif Al Kadri (Postgraduate, University of Mataram, 2026)
Teacher work motivation plays a crucial role in enhancing instructional quality and achieving educational goals. This study examined the influence of Principal Supportive Leadership and School Environment on Teacher Work Motivation among public junior high school teachers. A quantitative research design was employed using simple and multiple linear regression analyses. The study involved 276 teachers selected through proportionate stratified random sampling from 47 public junior high schools in a regency of West Sumatra Province, Indonesia. The sample size was determined using the Cochran formula. Data were collected using structured questionnaires and analyzed using IBM SPSS Statistics version 23. The findings revealed that Principal Supportive Leadership had a positive and significant influence on Teacher Work Motivation. Similarly, School Environment significantly influenced Teacher Work Motivation. The simultaneous analysis demonstrated that both variables jointly explained Teacher Work Motivation better than either variable individually. These findings highlight the complementary roles of supportive leadership and a positive school environment in fostering teachers’ motivation. The study contributes to the educational leadership literature by providing empirical evidence that organizational conditions are important determinants of teacher work motivation and by offering practical implications for developing supportive school leadership and collaborative learning environments.